Evaluation of African catfish Clarias gariepinus responses to graded levels of zinc practical diet (2016)
Fisheries and aquaculture contribute significantly to food security and livelihood; therefore, fish and fish products are projected as being among the most widely traded foods. Fish like other animals has requirement for essential nutrients in order to grow properly. Such essential foods are available in the wild for fish to forage extensively to meet their body needs. The variable factors such as climate change, environment, season of the year and location among others determines the abundance and search for these foods. These factors modifies aquatic environment and make it difficult for fish in the wild to forage adequately. Therefore, enough food in the form of artificial diet is required to furnish fish with the nutrients it need out of its natural environment for optimal growth. However, most of the challenges facing the formulation of feed are on the affordability, ready acceptability and bioavailability for fish optimal growth. Therefore, trace minerals which are needed in minute quantity at a time for the general health maintenance and growth of an animal offers a soft landing to this challenges; however, their deficiency perturbs the wellbeing of the fish. Zinc has been recognized to play a vital role in almost every aspect of living system either directly or indirectly. The biochemical components of fish diet that needs varying in terms of percent inclusion to render the protein in feed more bioavailable should be encouraged. The objectives of this study includes determination of the; required dietary zinc inclusion that is essential for juvenile African catfish Clarias gariepinus growth, serum biochemical profile of African catfish juveniles post feeding response to growth, and haematological responses of African catfish (Clarias gariepinus) to graded levels of zinc nutrient. Growth performance, serum biochemistry and physiological response to graded levels of practical dietary zinc fed to African catfish (Clarias gariepinus) juvenile were investigated. Water quality was monitored throughout the period of the study and the results showed that all parameters were within the required and tolerable ranges for catfish. The mean weight of fish fed dietborne zinc nutrients revealed that there were no significant differences in growth responses to graded levels of dietary zinc inclusions of 0, 5.46, 10.96, 16.40, 21.86 and 27.33mg Znkg-1 . The results for the mean weight revealed that there are no significant variations in mean weight since P>0.05. However the mean weight for the diet increased with respect to dietary zinc inclusion (Figure 1). The SGR, FCR, GFCE, F.I and RGR, also showed no significant variations among fish fed. The PCV revealed that there are no significant variations among the values for the fish fed with Diets 3, 4 and 5. The serum biochemistry revealed significant variations in the serum total protein (T,P) among fish fed on all the Diets, with the highest values in fish fed Diets 4 and the minimum values in fish fed Diet 2. Fish fed dietary zinc had slightly altered haematological and serum biochemistry in response to dietary zinc.